THE RELEVANCY OF ENGLISH IN CONTEXT FOR SMA/MA STUDENT YEAR ONE TEXTBOOK TO THE CURRICULUM USED - Nisak, Qudwatin (Englisia Journal, 2013)
To improve the quality of English education in Nanggroe Aceh Darussalam (NAD), the Department of Education of NAD as policymaker has made some efforts, among others, sending some teachers for overseas training and also conducting in-service training in designing English teaching material. One of the results of the projects done by the Department of Education of NAD is an English textbook entitled "English in Context for SMA/MA student year 1", was distributed to some senior high schools in Banda Aceh in 2005. Lately, the textbook hasn't been used effectively. Based on that fact, it is considered necessary to evaluate the textbook in order to know its relevant to curriculum used. The data of this study are the contents of English in Context for SMA/MA students year 1, consist of objectives of the textbook, themes chosen, skills presented, task designed, types of the text, language focus provided, vocabulary, and just for fun sections as well as the physical condition of textbook. After the data were put based on their classifications, they were analyzed qualitatively by finding its relevancy to CBC. The relevant elements of textbook to CBC and the deficient element of the textbook were explained descriptively. The result shows that only small portions of suggested material in CBC are provided in the textbook. The types of listening texts which are relevant to CBC are only recount and report. The genre of the reading texts which are relevant to CBC are recount, report, and news items. Meanwhile, the speaking task types provided in the textbook are dialogue, talks/speeches, plays/role play, discussion, and report. The deficient elements found in the textbook are lack of clarity of the authors' objective, repetition of the tasks designed, lack of variation in some skill's presentation and some irrelevant materials to CBC.